2015
DOI: 10.1590/s1679-45082015rw3147
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the pool of kidney donors: use of kidneys with acute renal dysfunction

Abstract: Given the shortage of organs transplantation, some strategies have been adopted by the transplant community to increase the supply of organs. One strategy is the use of expanded criteria for donors, that is, donors aged >60 years or 50 and 59 years, and meeting two or more of the following criteria: history of hypertension, terminal serum creatinine >1.5mg/dL, and stroke as the donor´s cause of death. In this review, emphasis was placed on the use of donors with acute renal failure, a condition considered by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
1
3
0
2
Order By: Relevance
“…In addition, Kumar et al [20] showed that 3-year graft survival was 90% in the AKI group (named as ARF), and this rate of survival was similar to that observed among standard criteria donor (SCD) kidneys and was higher in comparison to ECD kidneys. Similarly, data presented by colleagues from Brazil has demonstrated similar 5-year graft survival in AKI and non-AKI groups of 81% and 84% ( p =ns), respectively [21].…”
Section: Discussionsupporting
confidence: 54%
“…In addition, Kumar et al [20] showed that 3-year graft survival was 90% in the AKI group (named as ARF), and this rate of survival was similar to that observed among standard criteria donor (SCD) kidneys and was higher in comparison to ECD kidneys. Similarly, data presented by colleagues from Brazil has demonstrated similar 5-year graft survival in AKI and non-AKI groups of 81% and 84% ( p =ns), respectively [21].…”
Section: Discussionsupporting
confidence: 54%
“…In the context of RTx, contradictory data on the outcomes of kidneys with AKI have been published. There is a series of small studies yielding that despite higher rates of delayed graft function (DGF) in grafts from AKI donors, there is no significant difference in graft function and one-year survival after transplantation between kidneys with and without donor AKI [ 9 , 10 ]. In contrast, a retrospective analysis of the UK Transplant Registry including 11,219 kidneys (1,869 with AKI) reported a slightly lower graft survival of kidneys from donors with AKI along with higher rates of DGF and primary non-function [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It will be an important preclinical finding to address, because organs and patients are frequently taken care of after IRI starts. Additional strategies, such as hypothermic machine perfusion for a prolonged cold ischemia time, reduction of organ extraction time, and inclusion of older (≥60 years) female donors in conjunction with administration of estrogen, can significantly improve graft function and survival (13)(14)(15)(16)(17). The effect of estrogen administration needs to be investigated in large animals before human interventions are studied, as the role of the estrogen receptor in the protective mechanism remains undefined.…”
Section: Discussionmentioning
confidence: 99%